Hygiene mobile health unit - Prata, Rafaela Aparecida [UNESP]; Cogo Simao, Evelise Pires [UNESP]; Chadi, Paula Fernandes [UNESP]; Gregorio Tavares, Ana Lucia [UNESP]; Benedetti, Natalia Augusto [UNESP]; Orso, Livia Faria; Caldeira, Silvia Maria [UNESP]; Carvalho, Gabriela Correa; Correa, Ione [UNESP] (Fundacao Oswaldo Cruz, Escola Politecnica Saude Joaquim Venancio, 2016)
Introduction: Considering the spread of microorganisms in the transport and mobility of people in mobile health units, the cleaning and disinfec tion of all areas for accommodation of users and equipment is crucial. Objective: To identify scientific literature related to the hygiene of mobile health units. Method: This is an integrative literature review in the databases LILACS, SciELO, MEDLINE, PubMed, CINAHL, Embase, WoS, and Scopus. The data collection was carried out in March 2015, including articles from 2005 to 2015. Results: 769 articles were selected. From these, only six articles met the inclusion criteria: three from CINAHL, two from PubMed, and one from LILACS. All described international studies. Conclusion: It is necessary to carry out further investigations to aid in the cleaning of mobile health units by choosing the right disinfectant for the microbial load of these vehicles to provide strategies for preventing infection related to health assistance. Therefore, increasing good practices and even drafting care protocols or Standard Operating Procedures (POP) in the control of cross infection in mobile health units is vital.
Keywords: Disinfection; Infection; Infections; Ambulance; Ambulances